Reliability of parts and unrestorable components in the machine design - Yu. P. Manshin; E. Yu. Manshina (Advanced Engineering Research)
Introduction. The issues on standardization of reliability indices in the early stages of machine design are considered. This approach maintains thetarget level of reliability when developing parts that are critical in view of stable operation. The work objective is to study design problems in this area. The analysis of the reliability regulation methods suggests that they are insufficient to design. Besides, there are some contradictions associated with the use of the exponential failure law in design.Materials and Methods. At the stage of the task order, the numerical values of the operation time and reliability of the machine are determined. Then the values of the reliability probabilities or failures of the system and its elements are shown by exponential expressions. In them, degrees are the ranking parameters of the system reliability indices.Research Results. The alternative approach to normalization is synthesized; it enables to complete a full structural analysis. Thus, the reliability indices of the entire system or parts, whose operational safety determines the machine reliability, can be assessed. Parts and other components, whose failures are not sudden, are considered without using the exponential law. This preserves the inherent simplicity of mathematical operations.Discussion and Conclusions. The numerical value of the reliability probability (RP) of the machine as a whole, taken at the stage of the task order, is insufficient for the reliability target design. The specified RP and running time of the system elements, which are sources of failures developing according to different laws, are required. The results obtained can be used both in designing new mechanical systems with the reliability target, and in the modernization of machines.